Current State and Development Prospects of the Russian Economy - Rodionova, Irina; Kokuytseva, Tatiana (Quaestiones Geographicae, 2011)
The article characterises changes that have occurred in the economy of Russia and its foreign trade over the recent years. It estimates the country's position in the world ranking. The process of Russia's involvement in integrated world economic development after the collapse of the socialist system has been far from simple, because it was simultaneous with the country's system transformation and economic restructuring. The economy of modern Russia operates in difficult conditions. In the 20th century the burden of the socialist period of the country's development combined with the mistakes of the structural economic transformation of the 1990s already generated new systemic disproportions which have greatly modified the entire economic complex of the country. An analysis of the Russian share in the production of principal types of industrial products over the last three decades as well as a comparison of particular development indicators of the largest world economies and the share of countries and country groups in the world's high technology production reveals a weakening of the Russian position in the world economy. The article also presents changes in Russia's foreign trade and the decrease in its main economic indicators in the conditions of the current world financial crisis. The article underlines the necessity of change in the current model of Russian participation in the globalising world towards a search for a new place in the world economy and the world market, and, first of all, in knowledge-intensive industries and the sphere of high technology.